1998
DOI: 10.1002/(sici)1096-8628(19980605)77:5<360::aid-ajmg4>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Rarity of PIT1 involvement in children from Russia with combined pituitary hormone deficiency

Abstract: To ascertain the molecular background of combined pituitary hormone deficiency, screening for mutations in the pituitary-specific transcription factor (Pit-1/GHF-1) gene (PIT1) was performed on a cohort of 15 children from Russia with combined growth hormone (GH)/prolactin (Prl)/thyroid-stimulating hormone (TSH) deficiency. The group of patients, suspected of PIT1 mutations, consisted of four familial cases (seven patients) and eight sporadic cases. All had complete GH deficiency and complete or partial Prl an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 23 publications
0
28
0
3
Order By: Relevance
“…This is the first functional analysis of Pit-1 with mutations in the transactivation domain found in patients with CPHD (19,20). The case reported by Fofanova et al (19) was a 3-year-old girl who showed total GH/PRL and partial TSH deficiency without mental retardation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is the first functional analysis of Pit-1 with mutations in the transactivation domain found in patients with CPHD (19,20). The case reported by Fofanova et al (19) was a 3-year-old girl who showed total GH/PRL and partial TSH deficiency without mental retardation.…”
Section: Discussionmentioning
confidence: 99%
“…Neither P14L nor P24L Dominantly Inhibited the Transcriptional Activity of Wild Type Pit-1-Because both of the probands with P14L or P24L were found to be heterozygous for these mutations (19,20), it has been hypothesized that P14L and P24L might inhibit the activity of the wild type Pit-1 (21)(22)(23). To test the ability of these mutants to interfere with the transactivation of Pit-1-targeted gene expression by wild type Pit-1, the expression vector for P14L or P24L was transfected into COS7 cells together with the PRL-Luc and wild type Pit-1 expression vector.…”
Section: A-c)mentioning
confidence: 99%
See 3 more Smart Citations